TEACHING THE MEANING OF RAMADHAN TO STUDENTS OF MIFTAHUL JANNAH ORPHANAGE IN INCREASING EMPATHY TOWARDS OTHERS - Likdanawati; Hamdiah; Sutriani; Reza Juanda; Risna Dewi; M.Subhan (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This study investigated effective methods to teach the meaning of Ramadhan to children at Miftahul Jannah Orphanage to enhance their empathy towards others. Traditional approaches to Ramadhan education often focus on rituals, potentially neglecting the social and humanitarian aspects. This study explored the use of experiential learning, social activities, and engaging media to foster empathy and a deeper understanding of the spiritual and social values ​​of Ramadhan. The results showed that these methods significantly improved understanding of the meaning of Ramadhan and encouraged positive behavioral changes, increasing social sensitivity and empathy among children. This study highlights the importance of innovative and contextual approaches in religious education to foster caring and socially responsible individuals.